2015
DOI: 10.1111/cmi.12540
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 17-5p regulates autophagy inMycobacterium tuberculosis-infected macrophages by targeting Mcl-1 and STAT3

Abstract: Autophagy plays a crucial role in the control of bacterial burden during Mycobacterium tuberculosis infection. MicroRNAs (miRNAs) are small noncoding RNAs that regulate immune signalling and inflammation in response to challenge by pathogens. Appreciating the potential of host-directed therapies designed to control autophagy during mycobacterial infection, we focused on the role of miRNAs in regulating M. tuberculosis-induced autophagy in macrophages. Here, we demonstrate that M. tuberculosis infection leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 56 publications
0
79
0
Order By: Relevance
“…6G). MiR-17 has been shown to target STAT3 3’UTR and regulate STAT3 expression, thereby, leading to a loss of suppressive function in myeloid-derived suppressive cells (35, 36). Consistent with the previous findings, an overexpression of miR-17 reduced the nuclear translocation of p-STAT3 in TNF-α-stimulated RASFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6G). MiR-17 has been shown to target STAT3 3’UTR and regulate STAT3 expression, thereby, leading to a loss of suppressive function in myeloid-derived suppressive cells (35, 36). Consistent with the previous findings, an overexpression of miR-17 reduced the nuclear translocation of p-STAT3 in TNF-α-stimulated RASFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that miR-17 may regulate TNF-α signaling at multiple steps in RA and its influence on TRAF2 and cIAP2 may be the earliest and most prominent in TNF-α signaling pathway. In addition, recent studies have shown that miR-17 targets STAT3 3’UTR to regulate its expression in myeloid-derived suppressive cells and in other cell types (35, 36), suggesting STAT3 regulation may be a downstream direct effect of miR-17 through 3’UTR binding.…”
Section: Discussionmentioning
confidence: 99%
“…As a class of small noncoding RNA molecules that can suppress gene expression by targeting mRNAs for translational repression and/or cleavage, miRNAs have been shown to be involved in disc degeneration [15]. It has been reported that miRNAs are able to regulate autophagy in multiple types of cells, such as colorectal cancer cells [158], gastric cancer cells [159], macrophages [160], and tubular epithelial cells [161].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, the impact of autophagy on M. tuberculosis is complicated. It has been reported that enhanced autophagy is capable of promoting M. tuberculosis survival (Kumar et al, 2015), whereas nordihydroguaiaretic acid (NDGA) and α-mangostininduced autophagy can inhibit the replication of M. tuberculosis in infected macrophages derived from the human THP-1 cell line (Guzmán-Beltrán et al, 2015). Furthermore, the impact on apoptosis and autophagy exerted by PRRSV might be different in vivo and in vitro and change with various target cells.…”
Section: Immune Evasion Strategiesmentioning
confidence: 99%